Anthropometry does not fully explain low fitness among adults with Down syndrome. Issue 4 (17th January 2021) - Beck, V. D. Y.; Baynard, T.; Lefferts, E. C.; Hibner, B. A.; Fernhall, B.; Hilgenkamp, T. I. M.
Abstract: Background: Cardiorespiratory fitness, expressed as peak oxygen uptake during exercise (VO2 peak), is an important predictor of cardiovascular health and is related to anthropometry in the general population. Individuals with Down syndrome (DS) have reduced cardiorespiratory fitness and often exhibit different anthropometrics compared with the general population. Interestingly, the relation between anthropometry and cardiorespiratory fitness found in the general population is not apparent in individuals with DS. However, accurate measures with dual energy X‐ray absorptiometry (DEXA) scan have not been used to investigate this relationship in this population. The purpose of this paper was to investigate the relationship between accurate measures of anthropometry and cardiorespiratory fitness in adults with DS compared with an age‐matched and sex‐matched control group. Methods: Anthropometrics (height, weight, waist and hip circumference, body composition via DEXA) and cardiorespiratory fitness (VO2 peak, measured during a graded maximal exercise test) were assessed in adults with ( n = 9; 25 ± 3 years; 6 male patients) and without DS ( n = 10, 24 ± 4 years; 5 male patients). Results: Participants with DS were shorter ( P < 0.01) than without DS and had a higher body mass index ( P < 0.01), waist circumference (WC) ( P = 0.026) and waist/height ratio (WHtR) ( P < 0.01), but similar weight, body surface area (BSA), waist/hip ratio and body composition ( P > 0.05). Participants with DS had significantly lower relative VO2 peak and VO2 peak corrected for total lean mass (TLM), but similar absolute VO2 peak, compared with without DS. In participants with DS, only WC and WHtR were associated with VO2 peak, whereas in participants without DS, height, weight, BSA, TLM, leg lean mass and body fat percentage were associated with VO2 peak. Conclusions: These results suggest that the relation between anthropometry and cardiorespiratory fitness found in the general population is not the same in adults with DS and that anthropometrics do not fully explain cardiorespiratory fitness in adults with DS. Further research into potential alternative explanations is required.